So sánh đặc trưng cấu trúc và hoạt tính của hai hệ xúc tác spinel NiAl và CoAl trong phản ứng khử chọn lọc khí NO bằng C3H8 - Ngà, Nguyễn Kim; Chi, Đặng Kim (Vietnam Journal of Chemistry, 2014)
A comparison of structure behavior of NiAl and CoAl spinels prepared via sol-gel process is investigated. Characterization of the prepared spinels has been determined by using a variety of techniques such as XRD, UV-VIS, TPR-H2and nitrogen adsorption-desorption isotherms. The results shown that these spinels possessed different structure and as a result their catalytic performance was relatively diverse in C3H8-SCR-NO in the presence of excess oxygen.